2017
DOI: 10.1007/s00345-017-2078-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Fuhrman grade and age for cancer-specific and overall survival in patients with papillary renal cell carcinoma: results of an international multi-institutional study on 2189 patients

Abstract: FG is a strong prognostic factor for CSS in papRCC patients. In addition, patients older than 75 have worse CSM than patients younger than 50 years. These findings should be considered for clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…In accordance with published data, our study confirmed the impact of Fuhrman grade and status of surgical margins on survival [ 21 , 22 ]. Our results also agree with studies by Ficarra et al and Patard et al [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with published data, our study confirmed the impact of Fuhrman grade and status of surgical margins on survival [ 21 , 22 ]. Our results also agree with studies by Ficarra et al and Patard et al [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…From our perspectives, several points should be noted when we take the prior findings into consideration. Firstly, some studies investigated the prognosis of the subtypes after the data were adjusted against the effects of Fuhrman grade [10,20]. Delahunt et al indicated that Fuhrman grading was inappropriate for PRCC and recommended WHO/ISUP grading system [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of an increase in the size of the renal mass during follow-up, the previously postponed treatment (surgery or ablation therapy) was initiated [28,29]. In addition to the size of the mass, its FG was shown to be connected to the prognosis of RCC subtypes [31]. However, currently, no tumor markers have been discovered that could provide insight about the FG of renal masses preoperatively.…”
Section: Discussionmentioning
confidence: 99%